PENERAPAN METODE INKUIRI DALAM PEMBELAJARAN BAHASA INGGRIS DI MTs NURUSSAADAH POLTANGAN JAKARTA SELATAN - Sjafty Nursitti Maili; Yosi Maeleona Passandaran (JUDIKA (JURNAL PENDIDIKAN UNSIKA), 2020)
ABSTRACTThe purpose of this research is to find and to describe the implemetation of inquiry method in Englishlearning proces in MTs Nurussaadah Poltangan. It will be found the teachers’ obstacles in theinquiry method implementation. Inquiry method is a method focuses to the student’s ability to thinksistematicaly, critical and logicaly. The method of this research is describtive qualitative. The datawas taken from observation and interview results. The result showed that (1) the teachers in MTsNurussaadah Poltangan was uncommon to apply inquiry method in English learning. (2) theteacher’s obstacles in inquiry method implementation, such as uneffectiveness in numver of studentsin the classroom, lack of classroom facilities, and time duration. Keywords: Inquiry Method, English Learning, Implementation